Neurocysticercosis in Latin America: Current epidemiological situation based on official statistics from four countries - Rodríguez-Rivas, Roberto; Flisser, Ana; Norcia, Luiz Fernando [UNESP]; Filho, Pedro Tadao Hamamoto [UNESP]; Bonilla-Aldana, D. Katterine; Rodriguez-Morales, Alfonso J.; Carpio, Arturo; Romo, Matthew L.; Fleury, Agnès (Public Library of Science (PLoS), 2022)
Background Neurocysticercosis (NC) is one of the major parasitic diseases affecting the central nervous system and is endemic in much of Asia, sub-Saharan Africa, and Latin America. Its epidemiology is difficult to assess, although official registries are available in Brazil, Colombia, Ecuador, and Mexico. Methodology/Principal findings Using official statistics, we assessed trends in NC hospitalization rates during 1998–2019 in Brazil and Ecuador, during 2004–2019 in Mexico, and during 2009–2019 in Colombia. We also assessed the trend in NC mortality in Brazil (1998–2019), the trend in hospitalizations for NC in a Mexican tertiary-level hospital (Instituto Nacional de Neurología y Neurocirugía [INNN]; 1995–2019), and in Mexican primary care ambulatory clinics (1995–2019). Associations between NC hospitalization rates and the human development index (HDI) were also examined. In Brazil, Ecuador, and Mexico, statistically significant decreases in NC hospitalization rates were observed. In Mexico, a significant increase in the age of patients at INNN was observed, suggesting a decreasing incidence of recent infection. Conversely, a significant increase in NC hospitalization rate was observed in Colombia. HDI was not significantly associated with NC hospitalization rates when adjusting for time. Conclusions The downward trends in NC cases in Brazil, Ecuador, and Mexico are encouraging, especially in the context of the PAHO/WHO plan of action to eliminate neglected tropical diseases from the region. On the other hand, in Colombia, the increased NC hospitalization rate is concerning and needs further evaluation so that the authorities can take specific measures. These results should encourage health authorities in other endemic countries to establish a system of official registries to identify where the need for a control program is most urgent. However, it is also important to remember that NC persists, although less frequently in some Latin American countries, and efforts to achieve its control must continue.